Exact Controllability Implies Completely Stabilizability of Perturbed Linear Time-Varying Nonlocal System in the Real Hilbert Space - alghraby, haitham; Radhi A. Zaboon; Naseif J. Al-Jawari (Al-Qadisiyah Journal of Pure Science, 2021)
This paper deals with the problem of controllability and stabilizability of the perturbed linear time-varying nonlocal system defined in some suitable real Hilbert space. The aim of this paper is to show that any globally null-controllable system is completely stabilizability and conversely, under some additional conditions the complete stabilizability implies global null-controllability.